Development of an optimum mixture of ultra-high performance concrete. Issue 9 (20th October 2016) - Ahmad, Shamsad; Hakeem, Ibrahim; Maslehuddin, Mohammed
Abstract : Existence of ultra-high performance concrete (UHPC) is the result of one of the latest advances in concrete technology. As compared to the normal concrete mixtures, the mixtures of UHPC are reported to have several times more strength, elastic modulus, fracture toughness, ductility and durability. UHPC is prepared by mixing high amounts of cement and silica fume with fine quartz sand, quartz powder and fibres. The water to binder ratio is kept very low and therefore a high dosage of superplasticizer is needed to maintain the required flowability. Need for a fine quartz sand and quartz powder for producing UHPC mixtures increases the cost of UHPC in places where these ingredients are not naturally available. In the present study, an attempt was made to develop an optimum mixture of UHPC using readily available local fine dune sand. The local dune sand was used collectively as a natural mixture replacing fine quartz sand and quartz powder. To select an optimum UHPC mixture, several trial mixtures were considered by varying the proportions of the ingredients of UHPC. An optimum mixture of UHPC was selected based on optimum flow (above 180 mm), strength (above 150 MPa) and lower amounts of silica fume and steel fibres to reduce the unit cost. A series of tests were conducted on the specimens prepared with the optimally selected mixture of UHPC for determining its mechanical properties and durability characteristics including resistance against reinforcement corrosion and sulphate attack. Test results indicate an excellent performance of the optimum mixture of UHPC developed through the present work.